Pelaksanaan Rehabilitasi Pecandu Narkoba Melalui Media Terapi Musik Sebagai Bentuk Implementasi Pasal 54 Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika di Lembaga Pemasyarakatan Kelas I Way Huwi Provinsi Lampung - Zainudin Hasan (Universitas Bandar Lampung (UBL), 2017)
Drug abuseis increasing every year into serious attention by the government, In order to realize the Indonesian government program free of drugs through rehabilitation addicts very helpful in the prevention of drug crime. Based on Article 54 of Law Number 35 Year 2009 on Narcotics, which Narcotics addicts and Narcotics abuse victims are required to undergo medical rehabilitation and social rehabilitation, to recover the drug addicts in order to return to normal life in the midst of society. Researchers focus on research on social rehabilitation process where in Class IIA Narcotics Prison Class Way Huwi Lampung Province, is more to the religious approach and therapy. While the model of rehabilitation of drug addicts through social rehabilitation, researchers try to do a new rehabilitation method is through music therapy that has two models of active music therapy and passive music therapy. In the active music therapy patients are invited to sing, learn to play using musical instruments, imitate the tones, even make a short song in other words patients interact actively with the music, while the patient's passive music therapy just listening quietly without doing any activity. This study aims to increase community participation in helping drug prisoners to be free from drug trafficking through social rehabilitation; especially through music therapy media to the future can help the government to help liberate the Indonesian people from the dangers of narcotics abuse.